Validation of a culturally adapted SACQ in Vietnamese higher education: evidence from a technological university - Lan Hoang Thi Quynh; Hanh Pham Hong; Ha Tran Thi Thanh (Institute of Advanced Engineering and Science, 2026)
Grounded in Tinto’s theory of student integration, this study examines the structure of the student adaptation to college questionnaire (SACQ) in Vietnam higher education context, employed a cross-sectional quantitative approach. Data from 363 students at a technological university in Northern Vietnam were analyzed using exploratory and confirmatory factor analyses. Results yielded a refined 29-item scale (SACQ-29) with a five-factor structure, diverging from the original four-factor model. Most notably, social adjustment (SA) is separated into two distinct factors: one comprising positively worded items and another consisting predominantly of reverse-coded items, suggesting distinct adaptation mechanisms in digitally enhanced learning environments. Results revealed that students adapted most effectively to academic demands (M=5.77), but showed weak institutional attachment (IA) (M=3.14). Male students demonstrating significantly better overall adaptation than female students, and living arrangements also influenced adaptation levels, with students living with family showing poorer adaptation compared to others. Comparative analysis revealed high consistency between the SACQ-29 and the original SACQ-67 (r=0.925**). This study provides first validated Vietnamese SACQ, offering a practical tool for early identification of at-risk students and intervention design in contemporary higher education contexts.